Extraskeletal Ewing sarcoma attached to the ulnar nerve: A case report. (March 2021) - Sakuda, Tomohiko; Furuta, Taisuke; Johan, Muhammad Phetrus; Arihiro, Koji; Adachi, Nobuo
Highlights: EES involving the ulnar nerve is uncommon and extremely rare. EES in the ulnar nerve may mimic benign soft tissue tumor. Despite its rarity, high index of suspicion is advisable due to malignant nature. Wide excision and reconstruction is needed for EES involving ulnar nerve. Abstract: Introduction: Extraskeletal Ewing sarcoma (EES) of the extremity is uncommon, and only a small number of reported cases have been devoted to the upper-extremity. Presentation of case: A 65-year-old woman presented with a recurrent EES, a highly malignant tumor, involving the ulnar nerve at the right elbow region which was initially suspected as a benign soft tissue tumor, schwannoma, thus marginal excision had been performed. Due to its malignant behaviour, we treated the recurrent lesion with wide excision and reconstruction combined with chemotherapy. Histological evaluation revealed a monotonous small round cells appearance. Discussion: EES of the extremity involving the ulnar nerve is fairly uncommon. The tumor was often smaller in the adult than in the child population which was consistent with the present case, thus may mimic a benign tumor. Because of the overlapping histopathological features of EES with other tumors, other investigations such as immunohistochemistry and cytogenetic studies must be performed to allow definitive diagnosis. The result of our study was negative for the EWSR1-FLI-1 and CIC-DUX4 fusion gene, however, other less frequent translocations could be found in this case which does not exclude the diagnosis of Ewing sarcoma family. Conclusion: Few cases of EES involving the ulnar nerve have been previously reported. The correct diagnosis of EES involving the ulnar nerve has become particularly important in order to enable the initiation of comprehensive management that have the potential to reduce disease progression and the avoidance of improper and potentially harmful surgical therapy.